2017
DOI: 10.1177/2324709617697991
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban as an Antithrombotic Agent in a Patient With ST-Segment Elevation Myocardial Infarction and Left Ventricular Thrombus

Abstract: The incidence of left ventricular (LV) thrombi in the setting of an anterior myocardial infarction has declined significantly since the advent of primary percutaneous coronary intervention coupled with contemporary antithrombotic strategies in ST-segment elevation myocardial infarctions (STE-ACS). Despite oral anticoagulation with the currently accepted, standard-of-care vitamin K antagonist, warfarin, major bleeding complications still arise. Rivaroxaban is a novel, direct oral factor X anticoagulant that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
(13 reference statements)
0
17
0
2
Order By: Relevance
“…[30][31][32] The patient was initiated upon rivaroxaban for a myriad of reasons, including local accessibility, track-record in the SELECT-D trial, and prior cardiovascular experience in left ventricular mural thrombus dissolution. 33 The recommended dosage was instituted in addition to low aspirin and statin therapy as the multidisciplinary team considered the patient to be an advanced oncologic patient, given the metastatic thymic carcinoma and Khorana score of 3 coupled with an intermediate risk of bleeding as per the HAS-BLED scoring system. When cancer is included as an individual covariate along with components of the HAS-BLED score, it was considered the strongest predictor of major and overall bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] The patient was initiated upon rivaroxaban for a myriad of reasons, including local accessibility, track-record in the SELECT-D trial, and prior cardiovascular experience in left ventricular mural thrombus dissolution. 33 The recommended dosage was instituted in addition to low aspirin and statin therapy as the multidisciplinary team considered the patient to be an advanced oncologic patient, given the metastatic thymic carcinoma and Khorana score of 3 coupled with an intermediate risk of bleeding as per the HAS-BLED scoring system. When cancer is included as an individual covariate along with components of the HAS-BLED score, it was considered the strongest predictor of major and overall bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Nieman et al reported that anticoagulation with warfarin therapy can resolve fresh thrombi, but not chronic ventricular thrombi after MI (Niemann et al, 2012 ). However, several case reports have shown the feasibility of NOAC treatment of LV thrombi with dabigatran (Kaku, 2013 ; Nagamoto et al, 2014 ; Chung et al, 2015 ; Kolekar et al, 2015 ; Ohashi et al, 2015 ) or factor Xa inhibitors (Nakasuka et al, 2014 ; Padilla Pérez et al, 2014 ; Kaya et al, 2016 ; Makrides, 2016 ; Mano et al, 2016 ; Berry et al, 2017 ; Seecheran et al, 2017 ; Smetana et al, 2017 ). In the cases describing dabigatran to resolve LV thrombi, the doses varied between 110 and 150 mg bid and the resolution of the thrombi was confirmed after 3 weeks to 4 months (Hori et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose dabigatran due to the high bleeding risk of our patient and the availability of an efficient antidote (idarucizumab), which had shown rapid and complete reversion of the anticoagulant activity of dabigatran in the RE-VERSE AD study (Pollack et al, 2015 ). Only few cases have been reported in the literature where triple therapy was used to resolve a LV thrombus with Factor Xa inhibitors (Makrides, 2016 ; Mano et al, 2016 ; Berry et al, 2017 ; Seecheran et al, 2017 ; Smetana et al, 2017 ) or dabigatran (Chung et al, 2015 ; Ohashi et al, 2015 ). In contrast to these described cases, apparent development of a LV thrombus under dabigatran treatment has been published recently (Adar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-VKA direct oral anticoagulants (DOACs) are currently replacing VKA in several clinical indications, such as in patients with non-valvular atrial fibrillation (AF) where they were found to be either non-inferior or superior to VKAs. However, to our knowledge, there are no robust data on the use of DOACs for the treatment of LV thrombi, and all the available data are limited to individual case reports (4, 5).…”
Section: Introductionmentioning
confidence: 99%